Describing numerical variables: which are the most appropriate parameters to describe the data? - Duquia, Rodrigo Pereira (An Bras Dermatol, 2017)
The proper description of numerical variables is very important when presenting a set of data. Measures of central tendency and dispersion are used to adequately understand a set of numerical variables. Knowledge of the properties of these measures and their adequate use provide the reader with a better understanding of the results of a study.